Reference frames in spatial updating when body-based cues are absent. - He, Qiliang; McNamara, Timothy P.; Kelly, Jonathan W. (Memory & Cognition, 2018)
The current study investigated the reference frame used in spatial updating when idiothetic cues to self-motion were minimized (desktop virtual reality). In Experiment 1, participants learned a layout of eight objects from a single perspective (learning heading) in a virtual environment. After learning, they were placed in the same virtual environment and used a keyboard to navigate to two of the learned objects (visible) before pointing to a third object (invisible). We manipulated participants' starting orientation (initial heading) and final orientation (final heading) before pointing, to examine the reference frame used in this task. We found that participants used the initial heading and the learning heading to establish reference directions. In Experiment 2, the procedure was almost the same as in Experiment 1 except that participants pointed to objects relative to an imagined heading that differed from their final heading in the virtual environment. In this case, pointing performance was only affected by alignment with the learning heading. We concluded that the initial heading played an important role in spatial updating without idiothetic cues, but the representation established at this heading was transient and affected by the interruption of spatial updating; the learning heading, on the other hand, corresponded to an enduring representation which was used consistently.